Search for a heavy gauge boson W ' in the final state with an electron and large missing transverse energy in pp collisions at root s=7 TeV - Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; Hammer, J; et al. (2011)
A search for a heavy gauge boson W' has been conducted by the CMS experiment at the LHC in the decay channel with an electron and large transverse energy imbalance ETmiss, using proton-proton collision data corresponding to an integrated luminosity of 36 pb-1. No excess above standard model expectations is seen in the transverse mass distribution of the electron- ETmiss system. Assuming standard-model-like couplings and decay branching fractions, a W' boson with a mass less than 1.36 TeV/c2 is excluded at 95% confidence level. © 2011 CERN.